Akhlak Sebagai Perisai Di Tengah Perubahan Gaya Hidup Modern - Suaidi Suaidi (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2023)
This study aims to determine the function of morality as a light and guide of human life in an era that tends to change morals is very visible. Morals or manners have an important role in building a nation. The morals in question are akhlakul karimah or commendable morals. Someone who has good morals, then all his actions and behavior are good. In this way, a harmonious and peaceful life will be realized. One of the hadiths of the Prophet Muhammad, Saw, explained "Indeed in the Messenger of Allah there are good role models," To form and build a great nation, a nation that is safe, peaceful, instilling morals in each person is the most important part that is inseparable from the physical development program . The reality cannot be denied that in everyday life there are still disagreements which result in disputes, quarrels or hostilities due to clashes of opinions and interests between people. Mutual respect and love for each other almost disappear when human interests clash. Knowledge that is actually attached to the person contributes to humans to speak politely and humanely. However, it turns out that people who have knowledge show arguments against each other in formal and informal discussion forums, as if they are unable to provide education to the community with good morals.